Предмет: Математика,
автор: Alena17let
(х+2у)^2+(х-2у)^2 упростить выражение
Ответы
Автор ответа:
0
Здесь нужно использовать формулы сокращённого умножения:
(а-b)²=a²-2ab+b²
(а+b)²=a²+2ab+b²
Выражение приобретёт вид:
х²+4ху+4у²+х²-4ху+4у²=2х²+8у²
(а-b)²=a²-2ab+b²
(а+b)²=a²+2ab+b²
Выражение приобретёт вид:
х²+4ху+4у²+х²-4ху+4у²=2х²+8у²
Похожие вопросы
Предмет: Литература,
автор: zanaveskinaok
Предмет: Английский язык,
автор: ziminabella1627
Предмет: Математика,
автор: yegorovakatya
Предмет: Биология,
автор: yana14cat
Предмет: Математика,
автор: димасик44